Overview of the recent developments on Hg2+ recognition - Mahato, Prasenjit; Saha, Sukdeb; Das, Priyadip; Agarwalla, Hridesh; Das, Amitava (RSC Advances, 2014)
Adverse influences of mercury on living organisms are well known. Despite efforts from various regulatory agencies, the build-up of Hg2+ concentration in the environment is of serious concern. This necessitates the search for new and efficient reagents for recognition and detection of Hg2+ in environmental samples as well as for application in diagnostics. Among various detection processes adopted for designing such reagents, generally methodologies that allow associated changes in spectra properties are preferred for the obvious ease in the detection process. Significant changes in the electronic spectral pattern in the visible region of the spectrum also induce detectable changes in solution colour for naked-eye detection and are useful for developing reagents for in-field sample analysis with yes-no type binary responses. However, reagents that allow detection of Hg2+ with associated fluorescence on response are useful for detection of Hg2+ in environmental samples, as well as for use as an imaging reagent, for detection of cellular uptake. High spin-orbit coupling constant for Hg2+ along with its high solvation energy in aqueous medium poses a challenge in developing efficient reagents with fluorescence on response that work in aqueous medium/physiological condition. To get around this problem, several methodologies, like conversion of rhodamine derivative spirolactam to strongly fluorescent xanthenes that form on binding to Hg2+, chemodosimetric reaction for generation of a new luminescent derivative, have been adopted. Apart from these, modified charge transfer processes on binding to Hg2+ have also been utilized for designing reagents for optical detection of Hg2+. Immobilization of such reagents on solid surfaces also led to the development of self-indicating Hg2+ ion scavengers. All such examples are discussed in the present review.